The Relationship of Various Physical Activities To Menopausal Symptoms - Naurah Al’Ariqoh; Adek Amansyah; Meldawati Meldawati (Asian Journal of Social and Humanities, 2023)
The purpose of this study was to identify the relationship of various physical activities to menopausal symptoms in women aged 50-60 years in the work area of the Ujunggading Health Center. Research Method: This study uses a correlation research design with a cross sectional approach model with a sample of 75 respondents with a non-probability sampling method, namely using purposive sampling, data collection using GPAQ and MRS questionnaires, data analysis using correlation tests. Results: The results of the study of 75 respondents found the frequency distribution of respondents' characteristics with the most jobs as housewives, namely 23 people (30.7%), the most junior high school education was 20 people (26.7%), and the most menopause duration of 5-7 years, which was 36 people (48.0%). Showing that most respondents had moderate category physical activity 54 (72%) and most respondents experienced moderate category menopausal symptoms 37 (49.3%) There was a relationship between physical activity and menopausal symptoms with p value = 0.000 (p < 0.05). Conclusion: There is a relationship between physical activity and menopausal symptoms where the higher the physical activity carried out, the less menopausal symptoms are felt, menopausal symptoms can be reduced by routinely doing activities and exercising for 15 to 60 minutes every day